Field Performance Evaluation of Amorphous Silicon (a-Si) Photovoltaic Systems in Kenya : Methods and Measurements in Support of a Sustainable Commercial Solar Energy Industry - Duke, Richard D.; Graham, Shannon; Hankins, Mark; Jacobson, Arne; Kammen, Daniel M.; Osawa, Bernard; Pulver, Simone; Walther, Erika (World Bank, Washington, DC, 2014)
The study reviews the active market for photo-voltaic (PV) solar home systems (SHSs) in Kenya, with cumulative sales in excess of 100,000 units, and current sales of approximately 20,000 modules per year. It further identifies that small single junction amorphous silicon (a-Si) modules dominate the market, largely due to their lower retail price, relative to similar sizes of crystalline PV modules. Despite this commercial success, there is concern about the performance of single junction a-Si modules, both in terms of uneven technological quality record, and uncertain short-term degradation, which occurs when this type of PV module is initially exposed to the sun. The study confirms that modules made by two of the three companies dominating the Kenyan a-Si PV market, offer long-term performance, roughly compared to crystalline PV, confirming also that quality brands of single junction a-Si modules provide a highly cost-effective alternative to crystalline modules for SHSs, particularly for households only able to afford relatively small systems. The success of this brand, despite its considerably higher price per measured Wp, indicate that rural consumers are ill-equipped to compare the relative performance of different module brands, and that risks and limitations associated with these systems, suggest a cautious approach.